Experience in snuffbox arteriovenous fistulae for hemodialysis. - Lee, J.K.; Ahmad, T.S. (Malaysian Medical Association, 2000)

(untitled)
Sixty-five patients with "Snuffbox" arteriovenous fistulae for hemodialysis were reviewed. The procedure was performed under local anaesthesia as an outpatient procedure. It was done as a "standby" procedure for 41.5% of patients with Chronic Ambulatory Peritoneal Dialysis. 58.5% of patients had the procedure done for primary hemodialysis. Patency was assessed as presence of an engorged vein and presence of thrill. This was assessed routinely at 4 to 6 weeks after the procedure. Patency rate was noted to be 83%. The commonest complication was thrombosis of the arteriovenous anastomosis. Some patients required repeated procedure at a more proximal site. Further study to determine the blood flow rate provided by the anastomosis, and comparison with other anatomical sites is necessary.